Síndrome de Burnout en Docentes Universitarios en Tiempos de Pandemia Covid 19 (2021)
The present investigation will study the presence of Burnout Syndrome in the Antonio Nariño University professors during times of COVID 19, implying a questionnaire to determine what level they’re in and what relation it has with the APGAR familiar instrument to prove the dependence of both